2022
DOI: 10.1038/s41598-022-16664-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative host–pathogen associations of Snake Fungal Disease in sympatric species of water snakes (Nerodia)

Abstract: The ascomycete fungus Ophidiomyces ophiodiicola (Oo) is the causative agent of ophidiomycosis (Snake Fungal Disease), which has been detected globally. However, surveillance efforts in the central U.S., specifically Texas, have been minimal. The threatened and rare Brazos water snake (Nerodia harteri harteri) is one of the most range restricted snakes in the U.S. and is sympatric with two wide-ranging congeners, Nerodiaerythrogaster transversa and Nerodiarhombifer, in north central Texas; thus, providing an op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…In Texas, there is a paucity of data for Oo . Presently, six confirmed reports of Oo infections were made to Texas Parks and Wildlife (N. Rains & P. Crump, personal communications; see Harding et al, 2022 , Dryad repository: https://doi.org/10.5061/dryad.t76hdr83p ), one published study showed wide‐spread occurrence among contemporary populations of Nerodia in the upper Brazos River drainage (north central Texas) (Harding et al, 2022 ), and another estimated 15% prevalence among terrestrial and aquatic snakes via SYBR Green qPCR in northeast Texas (Lizarraga et al, 2023 ). Thus, there is a knowledge gap regarding Oo infection dynamics in this region, and it is unknown if Oo is naturally occurring and previously unrecognized, naturally occurring but emerging, or has recently spread into Texas (i.e., a novel pathogen).…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…In Texas, there is a paucity of data for Oo . Presently, six confirmed reports of Oo infections were made to Texas Parks and Wildlife (N. Rains & P. Crump, personal communications; see Harding et al, 2022 , Dryad repository: https://doi.org/10.5061/dryad.t76hdr83p ), one published study showed wide‐spread occurrence among contemporary populations of Nerodia in the upper Brazos River drainage (north central Texas) (Harding et al, 2022 ), and another estimated 15% prevalence among terrestrial and aquatic snakes via SYBR Green qPCR in northeast Texas (Lizarraga et al, 2023 ). Thus, there is a knowledge gap regarding Oo infection dynamics in this region, and it is unknown if Oo is naturally occurring and previously unrecognized, naturally occurring but emerging, or has recently spread into Texas (i.e., a novel pathogen).…”
Section: Introductionsupporting
confidence: 53%
“…We focused primarily on Nerodia spp. for three reasons: (1) the first confirmed report of Oo infection in Texas was from N. h. harteri , (2) the state contains several widespread species, and (3) to gain historical insight for Oo infection associations observed in contemporary Nerodia populations by Harding et al ( 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Host species highly susceptible to infection with high mortality from infection receive the most research attention upon disease emergence (Altizer et al, 2004; Lorch et al, 2016; McGuire et al, 2017; Voyles et al, 2007). Hosts less susceptible to pathogen infections with low mortality from infection (relative to highly susceptible host species) also do receive research attention, but typically only within the context of highly susceptible hosts (Cheng et al, 2021; Dhondt et al, 2013; Fischer et al, 1997; Harding et al, 2022; Pannkuk et al, 2021; Poorten & Rosenblum, 2016). Consequently, we know less about responses of less susceptible hosts, although they are also at risk.…”
Section: Introductionmentioning
confidence: 99%